Strategi Komunikasi Pemasaran UD. Mitra Taman Jalan Lapangan Golf Tuntungan II Kecamatan Pancur Batu dalam Meningkatkan Minat Konsumen - Solin, Ayu Erlina Br; Rasyid, Abdul (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research aims to explore the marketing communication strategies implemented by UD. Mitra Taman in an effort to increase consumer buying interest and achieve customer satisfaction. The location of the research was UD. Mitra Taman, Pancur Batu District, Deli Serdang Regency, Jalan Golf Tuntungan II. The research methodology uses a descriptive case study with a qualitative approach, including interviews, observation and documentation analysis. The research results show that UD. Mitra Taman has succeeded in implementing a marketing communication strategy based on the Marketing Mix 4P elements or marketing mix. The implementation of this strategy has made a positive contribution to the continuity and development of the company for 30 years. The Marketing Mix theory by Kotler and Armstrong is a strong basis for UD. Mitra Taman in managing and developing its business.This research provides practical insight and context on how marketing communication strategies can influence consumer purchasing interest and achieve customer satisfaction in the context of UD. Mitra Taman. The implications of the results of this research contribute to practical understanding for business stakeholders and provide a basis for researchers to deepen further studies in the marketing strategy domain.